Glycocalyx‐Like Hydrogel Coatings for Small Diameter Vascular Grafts. (17th April 2020) - Dimitrievska, Sashka; Wang, Juan; Lin, Tylee; Weyers, Amanda; Bai, Hualong; Qin, Lingfeng; Li, Guangxin; Cai, Chao; Kypson, Alan; Kristofik, Nina; Gard, Ashley; Sundaram, Sumati; et al.
Abstract: Novel biological vascular conduits, such as decellularized tissue engineered vascular grafts (TEVGs) are hindered by high thrombogenicity. To mimic the antithrombogenic surface of native vessels with a continuous glycosaminoglycan layer that is present on endothelial cells (ECs), a hyaluronic acid (HA) modified surface is established, to effectively shield blood platelets from collagen‐triggered activation. Using the amine groups present on 4 mm diameter decellularized TEVGs, a continuous HA hydrogel coating is built via a bifunctional thiol‐reactive cross‐linker, thereby avoiding nonspecific collagen matrix cross‐linking. The HA hydrogel layer recreates a luminal wall, "hiding" exposed collagen from the bloodstream. In vitro blood tests show that adhered platelets, fibrinogen absorption, and fibrin formation on HA‐coated decellularized TEVGs are significantly lower than on uncoated decellularized TEVGs. The HA surface also inhibits macrophage adhesion in vitro. HA‐coated decellularized syngeneic rat aortae (≈1.5 mm diameter), and TEVGs in rat and canine models, respectively, are protected from aggressive thrombus formation, and preserve normal blood flow. Re‐endothelialization is also observed. HA‐coated TEVGs may be an off‐the‐shelf small‐diameter vascular graft with dual benefits: antithrombogenic protection and promotion of endothelium. Abstract : To reduce thrombosis risk on small diameter (<6 mm) vascular grafts, hyaluronic acid is coated on the lumen of decellularized tissue engineered vascular grafts. This layer effectively shields platelets from collagen‐triggered activation, while allowing endothelial repopulation over time in vivo. Hence, hyaluronic acid–coated grafts may be an off‐the‐shelf small‐diameter vascular graft with dual benefits: antithrombogenic protection and promotion of endothelium.